Análise bioclimática do bairro do Renascença II São Luis-MA: realidade e perspectiva do conforto térmico em espaços externos - Trinta, Patrícia Vieira (2007)
The present research concerns about outdoor s thermal comfort conditions in hot-humid climate cities, understanding that life quality is a result of the urban object s type built for the human being in an environment with specific climate and morphological characteristics. It is presented as object of study the correlation between the neighborhood Renascença II s microclimate in São Luis /MA-Brazil, hot-humid climate city, and its urban morphological changes. As well as the thermal comfort s satisfaction level of its outdoor users. The research has as general goal to diagnosis the way these transformations caused by the urbanization influence the Renascença II s microclimate, identifying critical spots of the studied area, in order to contribute with land use recommendations based on bioclimatic architecture concepts and supply bases to urban design decisions adequate to the São Luis climate. It is presented as theoretical bases the urban climate, its concepts and elements. After that, the thermal comfort conditioners and its prediction models of thermal comfort sensation in outdoor are presented. The predictive models are presented along with bioclimatic assessment methods. Finally the use of bioclimatic assessment as an effective tool to identify places that need changes or preservation in order to seek environment quality. The applied methodology was based on the studies of Katzschner (1997), complemented by Oliveira s (1988) and Bustos Romero s (2001) studies that suggest an analysis and evaluation of maps of topography, buildings floors, land use, green areas and land covering, in order to overlap their characteristics and identify climate variable s measurements points; then a quantitative analysis of the climate variables (air temperature and humidity, wind speed and direction) of the chosen points takes place. It was perceived that Renaissance II has no permanence areas as squares or parks, its outdoor has little vegetation and presets high land impermeability and built density levels. The majority of the people interviewed said that was comfortable in a range of air temperature between 27,28ºC and 30,71ºC. The elaboration of a neighborhood master plan is important, which defines strategies for improvement of the life quality of its inhabitants